2019
DOI: 10.3389/fphys.2019.00384
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resveratrol on the Composition and State of Lipids and the Activity of Phospholipase A2 During the Excitation and Regeneration of Somatic Nerves

Abstract: It has been shown that in the somatic nerve’s lipids, both during excitation and transection, changes occur with the composition of individual phospholipids and in phospholipids fatty acids, which changes the phase state of the myelin and nerve fiber axolemma lipid bilayer. A main contribution in the nerve degenerative processes is dependent on the composition phospholipid’s fatty acid changes during the activation of both Ca 2+ -dependent and Ca 2+ -independent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, different RSV dosages preferentially activate SIRT1 or AMPK in vivo, further increasing the complexity of these pathways [ 113 ]. Besides the molecular mechanisms, studies based on preclinical neurodegenerative disease models reported positive effects of RSV in improving mitochondrial function and neurological symptoms [ 123 , 124 ]. More recently, the effects of RSV administration on mitochondrial respiration of skin fibroblasts from PMD-patients have been reviewed [ 125 ].…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%
“…However, different RSV dosages preferentially activate SIRT1 or AMPK in vivo, further increasing the complexity of these pathways [ 113 ]. Besides the molecular mechanisms, studies based on preclinical neurodegenerative disease models reported positive effects of RSV in improving mitochondrial function and neurological symptoms [ 123 , 124 ]. More recently, the effects of RSV administration on mitochondrial respiration of skin fibroblasts from PMD-patients have been reviewed [ 125 ].…”
Section: “One-size-fits-all” Approachesmentioning
confidence: 99%
“…The low bioavailability could be attributed to the interaction with the food matrix components on one side, or to the metabolic processes mediated by the liver, intestine, and gut microbiota on the other side. The lipophilic property per se does not oppose the clinical use of the respective compounds, because lipophilic substances could exert neuroprotective function thanks to their ability to penetrate within cellular membranes [124]. Moreover, alternative strategies for increasing the in vivo availability of polyphenols through their delivery via, e.g., encapsulation into nanocarriers or similar strategies, could increase their experimental and subsequent clinical use for supporting peripheral nerve regeneration and preventing secondary impairment after peripheral nerve injury, such as neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms of action of resveratrol on the nerve regeneration process is associated with its antioxidant ability, due to the leveling of the content of hydroxyl, superoxide, and other radicals. It has been speculated that changes in the content of PL and DAG, as well as the redistribution of fatty acids of various lipid fractions, have an effect on the protein lipid relationships and the orderliness of fatty acids (viscosity) in the myelin and axolemma of the nerve fiber [124].…”
Section: Stilbenesmentioning
confidence: 99%
“…It is known that the accumulation of LPO products in myelin leads to changes in the activity of ion-transporting systems, altered protein conformations, the appearance of nonselective ion channels, and a change in microviscosity, which disrupt the normal functioning of the nerve fiber, as well as changes in the individual composition of phospholipids and fatty acids, which alter the phase characteristics of the membrane [12, 13].…”
Section: Introductionmentioning
confidence: 99%